Analisis Kurva Produksi: Hubungan Antara Faktor Produksi Modal dan Tenaga Kerja Dalam Meningkatkan Produktivitas - Khairani Alawiyah Matondang; Sijabat, Angel Monica; Simamora, Jonrian; Rizki, Mutiara Nailah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Productivity is a key element in the success of an organization in producing goods or services. This research aims to analyze the relationship between production factors, namely capital and labor, in increasing productivity using the Isoquant and Isocost curve approach, finding the optimal point of combination of capital and labor that produces maximum output with minimum costs, and understanding the decreasing phenomenon that occurs in increasing one factor of production excessively without being balanced by other factors. This research uses a quantitative and graphical approach to analyze the relationship between capital and labor. Analysis is carried out using Isoquant and Isocost curves, which represent the optimal combination of the two production factors. The data used comes from hypothetical case studies, where varying combinations of labor and capital are applied to provide their impact on productivity. Research finds that capital and labor have a complementary relationship. Increasing one production factor requires adjustments to other factors to achieve optimal efficiency in the production process.